Applicability of a health literacy test from the U.S. in a South African population - Lecoko, Motlalepule Lebogang Elizabeth (Rhodes University, Faculty of Pharmacy, Pharmacy, 2001)
This thesis investigates the suitability and applicability of a health literacy test from the U.S. in a black, Xhosa-speaking, South African population. The concept of literacy is a controversial one which has been much debated, as it is not easy to classifY people as simply either literate or illiterate. As a result there are a number of definitions of literacy that vary with purpose and culture, but the most common one is that a person is literate if he/she can read and write. Estimating literacy from years of schooling is an inexpensive method but is also unreliable, since people generally read 3 to 5 grades below their stated educational level. This method affords little insight into the ability of patients to adequately function in a health care enviromnent, an ability which is referred to as functional health literacy. A number of health literacy tests such as the REALM (Rapid Estimate of Adult Literacy in Medicine) test have been developed to assess this skill. The REALM test is a word recognition test which places people into a relevant grade range estimate according to the number of words pronounced correctly. It appears to assume understanding of the word if the person is able to read that word correctly. In this project 125 black Xhosa-speaking respondents of varying educational levels who were literate in English were interviewed with the aid of an interpreter. Comprehensive demographic data were collected. Respondents were first asked to read all 66 words aloud during which time pronunciation was checked, and thereafter they were asked to explain each word. It was found that the ability to automatically decode and read the words did not necessarily guarantee comprehension of these words. Many of the words proved to be unfamiliar to the majority of the Xhosa respondents who were able to pronounce them correctly, but could not explain them. These tended to be phonetically transparent words which were therefore more accessible to the unfamiliar reader. This research has proven to be of great value in helping identify such words which should be substituted with simpler words for use in health information materials. A number of words could neither be pronounced nor understood by the population majority and, interestingly, a small group of words could not be pronounced but were satisfactorily explained by some respondents. The results showed an extremely poor correlation between the stated educational level and the REALM grade range estimate. This emphasizes the inappropriateness of years of formal schooling as an indicator of functional health literacy. The criteria were established for deciding cases in which the REALM test could be applied (or succeeds) and when it is inapplicable (or fails). It was found to be inapplicable in 41% of cases which clearly indicates that, in its current form, it is not a valid, reliable test to use in determining health literacy in this English second language population. It can, however, be used as a basis fur the development of a more appropriate test. Recommendations for future research direction are presented and an alternative structure for a health literacy test is suggested.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Literacy; Literacy -- South Africa; Literacy -- Ability testing; Reading -- Ability testing